Effect of matrix metalloproteinase inhibitor on disrupted E‐cadherin after acid exposure in the human nasal epithelium. (17th October 2017) - Kim, Byoungjae; Lee, Hyun‐Ji; Im, Nu‐Ri; Lee, Doh Young; Kang, Cha Young; Park, Il‐Ho; Lee, Seung Hoon; Lee, Sang Hag; Baek, Seung‐Kuk; Kim, Tae Hoon
Abstract : Objective: Laryngopharyngeal reflux disease (LPRD) is one of potential factors in recalcitrant chronic rhinosinusitis with or without polyps. An increase in junctional permeability in the nasal mucosa in LPRD may be due to disrupted protein bridge formation with cell‐to‐cell adhesion molecules such as E‐cadherin. Despite the relationship between nasal mucosal inflammation and LPRD, the clear mechanism by which acid reflux affects the nasal epithelium remains unclear. Methods: The expression levels and distribution patterns of E‐cadherin in primary culture of nasal epithelial cells after acid exposure with or without dexamethasone and matrix metalloproteinase (MMP) inhibitor were determined using Western blot and immunocytochemistry. The functional roles of MMP inhibitor in maintaining junctional permeability in the nasal epithelium were elucidated by transepithelial permeability test. Results: By acid exposure to nasal epithelial cells, mature E‐cadherin was decreased and cleaved E‐cadherin was increased. This was thought to be caused by cleavage of mature E‐cadherin between cells and was confirmed by the increment of E‐cadherin inside a cell in immunocytochemical evaluation. Whereas disruption of E‐cadherin was not recovered by steroid medication with various treatments of dexamethasone, disrupted E‐cadherin was restored to normal by inhibition of MMPs with actinonin, a broad MMP inhibitor. This recovery was functionally demonstrated by transepithelial permeability test. Conclusion: Our results suggest that altered expression of E‐cadherin in the nasal epithelium by acid exposure may be a possible mechanism for nasal tissue injury in chronic nasal inflammation with LPRD, and that MMP inhibition is a potential treatment. Level of Evidence: NA. Laryngoscope, 128:E1–E7, 2018